Association between neuropathy and B‐vitamins: A systematic review and meta‐analysis. (15th March 2021) - Stein, Johannes; Geisel, Juergen; Obeid, Rima
Abstract: Background: Peripheral neuropathy (PN) is common in patients with diseases that are in turn associated with deficiency of the B‐vitamins, and vitamin treatment has shown mixed results. Methods: This systematic review and meta‐analysis studied the association between PN/pain and B‐vitamin biomarkers and investigated whether vitamin treatment can ameliorate the symptoms. PubMed and Web of Science were searched according to the study protocol. Results: A total of 46 observational and seven interventional studies were identified and included in the data synthesis. The presence of PN was associated with lowered B12 levels (pooled estimate [95% CIs] = 1.51 [1.23–1.84], n  = 34, Cochran Q Test I 2  = 43.3%, p  = 0.003) and elevated methylmalonic acid (2.53 [1.39–4.60], n  = 9, I 2  = 63.8%, p  = 0.005) and homocysteine (3.48 [2.01–6.04], n  = 15, I 2  = 70.6%, p  < 0.001). B12 treatment (vs. the comparators) showed a non‐significant association with symptom improvement (1.36 (0.66–2.79), n  = 4, I 2  = 28.9%). Treatment with B1 was associated with a significant improvement in symptoms (5.34 [1.87–15.19], n  = 3, I 2  = 64.6%, p  = 0.059). Analysis of seven trials combined showed a non‐significant higher odds ratio for improvement under treatment with the B‐vitamins (2.58 [0.98–6.79], I 2  = 80.0%, p  < 0.001). Conclusions: PN is associated with lowered plasma vitamin B12 and elevated methylmalonic acid and homocysteine. Overall, interventional studies have suggested that B‐vitamins could improve symptoms of PN. Available trials have limitations and generally did not investigate vitamin status prior to treatment. Well‐designed studies, especially in non‐diabetes PN, are needed. This meta‐analysis is registered at PROSPERO (ID: CRD42020144917). Abstract : Several component causes of peripheral neuropathy are associated with vitamin B12 deficiency that can itself cause neuropathy. Low plasma vitamin B12 and elevated plasma homocysteine and methylmalonic acid were found to be associated with the presence of neuropathy. Treatment with B12 in patients with neuropathy was associated with only slight symptom improvement.